Assessment of Intercostal Muscle Near-Infrared Spectroscopy for Estimating Respiratory Compensation Point in Trained Endurance Athletes - Salvador Romero-Arenas; Carmen Daniela Quero-Calero; Oriol Abellan-Aynes; Luis Andreu-Caravaca; Marta Fernandez-Calero; Pedro Manonelles; Daniel Lopez-Plaza (MDPI AG, 2023)
This study aimed to assess the reliability and validity of estimating the respiratory compensation point (RCP) in trained endurance athletes by analyzing intercostal muscles' NIRS-derived tissue oxygenation dynamics. Seventeen experienced trail runners underwent an incremental treadmill protocol on two separate occasions, with a 7-day gap between assessments. Gas exchange and muscle oxygenation data were collected, and the oxygen saturation breakpoint (SmO2BP) measured in the intercostal muscles was compared to the RCP, which was identified by the increase in the VE/<semantics><mover>V.</mover></semantics>CO2 slope and the point at which the PetCO2 started to decrease. No statistically significant differences were observed between the two methods for any of the variables analyzed. Bland-Altman analysis showed significant agreement between the NIRS and gas analyzer methods for speed (r = 0.96, p < 0.05), HR (r = 0.98, p < 0.05), <semantics><mover>V.</mover></semantics>O2 relative to body mass (r = 0.99, p < 0.05), and %SmO2 (r = 0.98, p < 0.05). The interclass correlation coefficient values showed moderate to good reliability (0.60 to 0.86), and test-retest analysis revealed mean differences within the confidence intervals for all variables. These findings suggest that the SmO2BP measured using a portable NIRS device in the intercostal muscles is a reliable and valid tool for estimating the RCP for experienced trail runners and might be useful for coaches and athletes to monitor endurance training.